2002
DOI: 10.1081/tma-120015622
|View full text |Cite
|
Sign up to set email alerts
|

Sims Study of the Calcium-Deprivation Step Related to Epidermal Meristem Production Induced in Flax by Cold Shock or Radiation From a GSM Telephone

Abstract: Exposing seedlings of the flax, Linum usitatissimum L., to a variety of weak environmental stresses plus a 2-day calcium deprivation triggers the common response of production of epidermal meristems in the hypocotyl. Here, we show that the same response was induced by a 1 min cold shock. Epidermal meristem production was also induced by a single 2-h exposure to radiation emitted at 0.9 GHz at non-thermal levels by a GSM telephone. This flax-based system is therefore well suited to studying the effects of low i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…The energy associated with the EMF radiation is extremely low 20 and insufficient to evoke plant defence mechanisms involving the genesis of free radicals or molecule ionization. Variations of cytosolic Ca 2+ concentration have been implicated after EMF stimulation 13 and might constitute the initial signal that evokes the observed molecular responses. Thermal effects 21 are unlikely to arise considering the frequency (900 MHz) and the very low power (0.1 W) dissipated in the large volume of the MSRC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy associated with the EMF radiation is extremely low 20 and insufficient to evoke plant defence mechanisms involving the genesis of free radicals or molecule ionization. Variations of cytosolic Ca 2+ concentration have been implicated after EMF stimulation 13 and might constitute the initial signal that evokes the observed molecular responses. Thermal effects 21 are unlikely to arise considering the frequency (900 MHz) and the very low power (0.1 W) dissipated in the large volume of the MSRC.…”
Section: Resultsmentioning
confidence: 99%
“…Plants may be appropriate experimental subjects, in the sense that they are highly sensitive to environmental signals [9][10][11] and plant studies raise less emotional concern than studies on animals or humans. Moreover, radiation from a GSM telephone or from a 105 GHz Gunn oscillator has been shown to have an effect comparable to that of a variety of environmental stimuli (such as manipulation stress, drought, wind and cold shock) in inducing physiological modifications (production of numerous epidermal meristems in the hypocotyls) or modifications of the proteome (pI shift, appearance or disappearance of a spot in 2D electrophoresis) in flax seedlings; [12][13][14][15] modifications of the proteome have also been observed in Arabidopsis seedlings subjected to stimuli such as cold shock or radiation from a GSM telephone. 15 Here, we have studied the effect of mobile-phone intensity microwave radiation on another type of plant (the tomato), taking a particular care to the conditions of irradiation and studying the accumulation of a stress-related transcript (mRNA) that responds very rapidly to even small environmental stimulations.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the growth of rice plants was enhanced with an electric fi eld of 28.5 kV m −2 compared to that without an electric fi eld (Rotcharoen et al, 2003), whereas a reduction in wheat and corn yield was observed in fi elds near hightension lines (Soja et al, 2003). Tafforeau et al (2002) showed that exposure to 900 MHz for 2 h resulted in induction of epidermal meristems and reduction in Ca 2+ , Na + , and K + contents; however, there was no change in the divalent to monovalent cation ratios. Atak et al (2003) reported that exposure to magnetic fi elds stimulated the root and shoot regeneration, and increased the fresh weight and total chlorophyll content in regenerated seedlings of soybean.…”
Section: Introductionmentioning
confidence: 97%
“…These depend on a multitude of diVerent (and uncontrolled) factors and are concerned with long-term eVects, thereby lessening the likelihood of a direct cause-eVect relationship (Boice et al 2002;Feychting et al 2005). Plants are rarely used in RF-EMF experiments (Selga and Selga 1996;TaVoreau et al 2002TaVoreau et al , 2004, partly because their very inertia makes the casual observer presume they are insensitive and thus unresponsive to their environment. In fact the opposite is more likely -their inability to escape the environment implies that plants must be able to sense subtle changes and adapt their responses accordingly Ferguson 2004).…”
Section: Introductionmentioning
confidence: 98%